Pengelolaan Bisnis Dan Manajemen Wirausaha Sentra IKM - Khaerul Umam; Reny Wardiningsih; Resty Yusnirmala Dewi; Feryansyah; Dina Amalya Putri; Eva Solina; Lalu Andika Noviawan (Universitas Mataram, 2026)
This community service activity aims to improve the knowledge and skills of Small and Medium Industry (SMI) Center managers in Central Lombok Regency in business and entrepreneurial management. The main problems faced by partners include a low understanding of business management, suboptimal financial management, a lack of clear division of tasks, and the limited use of digital technology in product marketing. The activity implementation method is carried out through three stages: preparation, implementation, and evaluation. The training activity was attended by 20 participants from four centers. The material provided covered human resource management, business financial management, and digital marketing strategies. The education and training method used a combination of lectures, discussions, questions and answers, as well as pre- and post-tests to measure the level of participant understanding. The results of the activity showed an increase in participants' understanding of the importance of structured business management, a clear division of tasks and responsibilities, separation of personal and business finances, regular financial records, and the use of social media as a marketing tool. In addition, participants will implement more professional and sustainable business management practices. This activity makes a positive contribution to strengthening the capacity of SMI Center managers, which is expected to increase productivity, expand market reach, and strengthen business competitiveness in the future.